New tools and methodologies for programming languages learning using the scribbler robot and Alice (2011)
Today is often raised the question, what happened to engineering? Each day are less aspiring to such programs, and we need to find innovative ways to motivate students, encouraging learning fun, and that his time, guaranteeing a solid covering topics that are usually evaluated in the first programming courses, some of the tools that were used during the experience at the University Icesi for teaching programming and Alice were Scribble robot, the which allowed students to interact with the fast world of programming. The teaching methodology had proven that through it the student can interact with a friendly interface that let users explore and use the concepts seen in the programming courses, encouraging students to improve their capacity through algorithmic understanding. Working with new strategies in the teaching of computer courses, is a fundamental pillar in the education of future engineers, given that capacity building fosters algorithmic analysis and problem solving skills as required by engineers. This paper will present the progress and results obtained using different programming interfaces and robots, as a complement to the basic algorithms and programming languages. It also will review the differences between traditional teachings vs. new tools for learning. © 2011 IEEE.